Design Thinking in STEM Classrooms: A Mixed-Methods Study on Enhancing Student Creativity - Rahayu, Ninik Sri; Huda, Nurul; Sari, Ira Wulan; Nampira, Ardi Azhar (Journal of Loomingulisus ja Innovatsioon, 2025)
Fostering creativity within Science, Technology, Engineering, and Mathematics (STEM) education remains a critical challenge, as traditional pedagogies often prioritize convergent thinking over innovative problem-solving. This study investigates the impact of integrating design thinking methodologies into STEM classrooms to enhance student creativity. The primary objective was to quantitatively measure changes in students’ creative abilities and to qualitatively explore their experiences and perceptions of the design thinking process. This research employed a sequential explanatory mixed-methods design. Initially, 120 secondary school students participated in a quasi-experimental study, completing pre-and-post Torrance Tests of Creative Thinking (TTCT). Subsequently, semi-structured interviews were conducted with a purposive sample of 20 students to provide deeper insights into the quantitative results. The findings revealed a statistically significant increase in students’ TTCT scores, particularly in the dimensions of fluency and originality. In conclusion, the integration of design thinking presents a robust pedagogical framework for systematically nurturing creativity in STEM disciplines, equipping students with essential skills for future innovation.